The influence of collaborative learning style, reciprocity and extroversion on knowledge sharing via social media among UUM undergraduates - Ng, Shu Kae (2016)
This quantitative study is aimed to study the relationship between collaborative learning style, reciprocity and extroversion on knowledge sharing via social media in Universiti Utara Malaysia (UUM). A total of 400 set of questionnaires were distributed to undergraduate students from three (3) academic colleges which are College of Business (COB), College of Arts and Sciences (CAS) and College of Law, Government and International Studies (COLGIS). However, only 363 set of questionnaires were return and usable for analysis. Regression analysis was performed to tests the hypotheses of the study. The result indicated that collaborative learning, reciprocity and extroversion were positively significant to knowledge sharing behavior via social media. The findings were discussed and recommendations for the future research were also addressed.